A Local Historical Museum in the Eyes of Its International Visitors: An Investigation into the Accessibility of Radya Pustaka Museum's Labels and Translation - Dyah Ayu Nila Khrisna; Ida Kusuma Dewi; Herianto Nababan; Bayu Budiharjo (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. Due to inadequate labeling, a museum's fundamental objective may be compromised. Museum Radya Pustaka Surakarta's unappealing and grammatically improper labels prompted us to study foreign visitors' perceptions of the English version of the museum labels. An analysis of the translation was carried out to see whether the flavor and essence of the original captions were preserved, the translation was under relevant cultural standards, and it could be read fluently or non-intrusively. This study used a descriptive qualitative design. Its data consisted of linguistic data, collected through questionnaires, in-depth interviews, and focus group discussions. The data were analyzed descriptively to answer the research questions on the naturalness and comprehensibility of label translation within the readers’ perception.  It has been discovered that the local Javanese cultural terminology makes it more difficult for foreigners to comprehend the labels. In addition, the naturalness of the translation is hindered by grammatical faults such as a lack of text coherence and an inadequate sentence structure. Remarkably, improperly designed museum labels and defects in the source text have also been proven to produce barriers to effective communication in translation. These facts may be inconvenient and fail to serve people from diverse cultural backgrounds. Due to this circumstance, the Radya Pustaka Museum in Surakarta needs to ensure that both the Indonesian and English museum labels it provides are of adequate quality to benefit its potential foreign visitors.Keywords: comprehensibility; culture; labels; museum; naturalness; translationAbstrak. Pemanfaatan label untuk mendeskripsikan benda-benda koleksi museum dapat membantu tercapainya tujuan museum sebagai pusat ilmu pengetahuan dan penelitian.  Tujuan tersebut akan sulit terwujud jika tidak tersedia label museum yang memadai.  Label di Museum Radya Pustaka Surakarta menjadi perhatian kami untuk melakukan penelitian tentang persepsi pengunjung asing terhadap terjemahan label museum dalam versi bahasa Inggris. Terjemahan tersebut dikaji untuk memastikan apakah rasa dan esensi teks asli dapat dipertahankan, apakah terjemahan mematuhi standar dan norma budaya sasaran, dan apakah terjemahan dapat mudah dipahami.  Hasil investigasi menunjukkan bahwa istilah-istilah budaya dalam bahasa Jawa menyulitkan wisatawan asing untuk memahami konten dalam label museum.  Permasalahan tata bahasa dan struktur kalimat yang kurang baik turut mengurangi tingkat keterbacaan terjemahan.  Selain itu, teks sumber yang kurang memiliki kesesuaian dengan tata bahasa Indonesia turut berkontribusi terhadap rendahnya kualitas terjemahan.  Temuan ini menunjukkan bahwa label museum belum dapat menjalankan fungsinya dengan baik sebagai media komunikasi dan penghubung antar budaya, khususnya dengan pengunjung yang memiliki latar belakang budaya yang berbeda. Oleh sebab itu, Museum Radya Pustaka Surakarta sebagai museum lokal sejarah masih memiliki pekerjaan rumah besar, yaitu menyediakan label museum yang mampu ‘memuaskan’ pengunjung internasional.Kata kunci: budaya, keberterimaan, keterbacaan, label, museum, penerjemahan